MEKANISME PERTAHANAN BAKTERI PATOGEN TERHADAP ANTIBIOTIK - Rina Hidayati Pratiwi (Jurnal Pro-Life, 2017)
The number of irrational for using antibiotics caused multidrug-resistant bacteria is increasing globally. The resistance of antibiotics are the condition that the influence of antibiotics as antiinfection useless or the pathogenic bacteria become unsensitive. That problem are failure of medicinal therapy for using antibiotics. This article reviews recent analize of the mechanisms by which bacteria survival pathogenic to antibiotics. The mechanism of bacterial resistance to antibiotics has been found to occur frequently by several cellular mechanisms, such as bacterial production of enzyme, mutation or exchange of plasmid or gene with low affinity to antibiotics, or decrease of cell wall permeability to antibiotics, the prevention of access to drug targets, changes in the structure and protection of antibiotic targets and the direct modification or inactivation of antibiotics. Keywords: antibiotics, resistance, mechanism, microorganisms